2023
DOI: 10.1371/journal.pone.0285275
|View full text |Cite
|
Sign up to set email alerts
|

Employees’ support strategies for mental wellbeing during and beyond the COVID-19 pandemic: Recommendations for employers in the UK workforce

Abstract: Throughout the COVID-19 pandemic, and beyond for many businesses, employees have had to adapt to new ways of working due to disruptions in traditional practices. It is therefore crucial to understand the new challenges that employees are facing when it comes to taking care of their mental wellbeing at work. To that end, we distributed a survey to full-time UK employees (N = 451) to explore how supported they felt throughout the pandemic, and to identify whether there are any additional types of support they wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Managers can also be offered training to support their staff with hybrid working. Mental health awareness training (BCT: information about health and emotional consequences) can be provided to managers to counter staffs' feelings of loneliness and uncertainty (Bailey et al, 2023); mental health training has been shown to impact managers' attitudes about, and understanding of, mental health (Dimoff et al, 2016). In Second, organisations can provide more infrastructure to support hybrid working through the allocation of physical resources (BCT: restructuring the physical environment) such as quiet rooms for disabled staff who might benefit from reduced noise/distraction (Taylor et al, 2022), office spaces and technological tools conducive to hybrid working teams (CIPD, 2022;Winkler et al, 2022) and a partnership with an established child care provider that can meet the needs of hybrid working parents/caregivers (Modestino et al, 2021).…”
Section: Barriers and Enablers To Hybrid Workingmentioning
confidence: 99%
“…Managers can also be offered training to support their staff with hybrid working. Mental health awareness training (BCT: information about health and emotional consequences) can be provided to managers to counter staffs' feelings of loneliness and uncertainty (Bailey et al, 2023); mental health training has been shown to impact managers' attitudes about, and understanding of, mental health (Dimoff et al, 2016). In Second, organisations can provide more infrastructure to support hybrid working through the allocation of physical resources (BCT: restructuring the physical environment) such as quiet rooms for disabled staff who might benefit from reduced noise/distraction (Taylor et al, 2022), office spaces and technological tools conducive to hybrid working teams (CIPD, 2022;Winkler et al, 2022) and a partnership with an established child care provider that can meet the needs of hybrid working parents/caregivers (Modestino et al, 2021).…”
Section: Barriers and Enablers To Hybrid Workingmentioning
confidence: 99%